2001
DOI: 10.1103/physrevlett.87.125901
|View full text |Cite
|
Sign up to set email alerts
|

Ge Self-Diffusion in EpitaxialSi1xGexLayers

Abstract: Diffusion coefficients and activation energies have been determined for Ge diffusion in strain-relaxed Si(1)-(x)Ge(x) with x = 0.00, 0.10, 0.20, 0.30, 0.40, and 0.50. The activation energy drops from 4.7 eV in Si and Si(0.90)Ge(0.10) to 3.2 eV at x = 0.50. This value compares with the literature value for Ge self-diffusion in Ge, suggesting Ge-like diffusion already at x approximately equal to 0.5. The effect of strain on the diffusion was also studied showing a decrease in diffusion coefficient and an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 21 publications
5
94
1
Order By: Relevance
“…5 In addition, the source/drain formation in sSOI is difficult due to the lower solubility and the higher diffusion coefficient of boron induced by the tensile strain. 6,7 On the other hand it was recently shown that flash lamp annealing ͑FLA͒ allows us to obtain ultrashallow p-junctions with high activation in bulk silicon. [8][9][10] Due to annealing times in the millisecond range, only the surface region of the samples is heated such that the bulk remains at a significantly lower temperature, essentially representing a heat sink.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, the source/drain formation in sSOI is difficult due to the lower solubility and the higher diffusion coefficient of boron induced by the tensile strain. 6,7 On the other hand it was recently shown that flash lamp annealing ͑FLA͒ allows us to obtain ultrashallow p-junctions with high activation in bulk silicon. [8][9][10] Due to annealing times in the millisecond range, only the surface region of the samples is heated such that the bulk remains at a significantly lower temperature, essentially representing a heat sink.…”
Section: Introductionmentioning
confidence: 99%
“…As RTA temperature increases, Ge diffusion becomes significant. 8,9,21 While Ge diffusion slightly increases with increasing RTA temperature, significant B diffusion took place, even at 950…”
Section: Resultsmentioning
confidence: 99%
“…Understanding of thermal behavior of Ge and B in B-doped Si 1-x Ge x layers is very important in designing appropriate device structures. 6,[8][9][10][11] Nondestructive monitoring of Ge content and B concentration, before and after subsequent high temperature process steps, would be very beneficial for device structure optimization and early detection of potential process related problems. Characterization of Si 1-x Ge x epitaxial layers using conventional techniques such as cross-sectional transmission electron microscopy (XTEM), Auger electron spectroscopy (AES), secondary ion mass spectroscopy (SIMS), double crystal X-ray diffraction and photoluminescence (PL) has been reported by Lafontaine et al 12 The reported techniques are invasive and time consuming, and not suitable for real time process monitoring which is a theme of this work.…”
Section: Introductionmentioning
confidence: 99%
“…The lattice kinetic Monte Carlo ͑LKMC͒ method is an efficient approach for simulating dynamical evolution in microscopic systems such as microstructural evolution in crystals, point defect clustering in silicon, 1-3 phase segregation in metallic alloys, 4,5 and surface morphological evolution during vapor deposition. [6][7][8][9] The primary advantage of LKMC is that it effectively circumvents the vibrational motion of atoms that is responsible for the temporal bottleneck in molecular dynamics.…”
Section: Introductionmentioning
confidence: 99%